2016
DOI: 10.1186/s40364-016-0073-4
|View full text |Cite
|
Sign up to set email alerts
|

JAK2 V617F mutation, multiple hematologic and non-hematologic processes: an association?

Abstract: BackgroundPopulation studies showed that patients with JAK2 V617F mutation had increased mortality, and increased risk of any cancer, hematologic cancer, and myeloproliferative disease.Case presentationA 68-year-old Asian male with JAK2 V617F mutation developed four different hematologic and non-hematologic neoplastic processes. In 2009, he was diagnosed with stage IA lung adenocarcinoma and also noted to have worsening leukocytosis and thrombocytosis with peak platelet count of 1,054,000/mL). Bone marrow biop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Importantly, the levels of JAK2 autophosphorylation and activation are increased in many cancers, particularly those of a haematopoietic origin. Several of these cancers harbour the JAK2 V617F mutant, which drives cell proliferation and can enable immune escape [50][51][52]. Inhibition of JAK2 using the non-selective compound AG490 has demonstrated that JAK2 activity is required for STAT3 phosphorylation and viral oncogene expression in HPV+ cervical cancer cells [47].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the levels of JAK2 autophosphorylation and activation are increased in many cancers, particularly those of a haematopoietic origin. Several of these cancers harbour the JAK2 V617F mutant, which drives cell proliferation and can enable immune escape [50][51][52]. Inhibition of JAK2 using the non-selective compound AG490 has demonstrated that JAK2 activity is required for STAT3 phosphorylation and viral oncogene expression in HPV+ cervical cancer cells [47].…”
Section: Discussionmentioning
confidence: 99%
“…10 There is only a rare case depicting the association of JAK2 V617F mutation with myeloproliferative, lymphoproliferative, and solid neoplasms. 24 Here, for the first time, we provide evidence that upregulation of JAK2 is associated with lung adenocarcinoma LN metastasis. Furthermore, downregulation of JAK2 was found to significantly suppress the proliferation, migration, and invasion of lung adenocarcinoma cells.…”
Section: Discussionmentioning
confidence: 61%
“…10 There is only a rare case depicting the association of JAK2 V617F mutation with myeloproliferative, lymphoproliferative, and solid neoplasms. 24…”
Section: Discussionmentioning
confidence: 99%